The Role of Exports, Inflation Management and Human Resources in Preparing for Golden Indonesia 2045 - Leksono, Ari Wahyu; Bratamanggala, Rudi; Saleh, Sugiyanto (Formosa Journal of Sustainable Research, 2024)
The research explores the critical roles of exports, inflation management, and human resource development in preparing Indonesia for its ambitious "Golden Indonesia 2045" vision. Against the backdrop of complex economic and social challenges, this study employs a comprehensive literature review to investigate the interconnected nature of these factors and their collective impact on the country's long-term development plans. The purpose is to determine how exports, inflation control, and investment in human capital can contribute to the realization of Indonesia's goals for economic growth, global competitiveness, and social inclusivity by 2045. The literature review methodology systematically examines academic sources to provide insights into current trends, strategies, and the interdependence of these key variables. The findings reveal that a balanced approach integrating export promotion, prudent inflation management, and strategic human resource development is essential for Indonesia to navigate the path towards its golden future. The research concludes with recommendations for policymakers and stakeholders on leveraging these critical elements to foster a stable, innovative, and globally influential Indonesia by 2045